Implementasi Strategi Pembelajaran Pendidikan Agama Islam - Zetty Azizatun Ni’mah (At-Tajdid: Jurnal Ilmu Tarbiyah, 2016)
inability of teachers in choosing learning strategies unvariaty will cause boredom student in learning is done, it is a serious impact on the psychological students. Because of that variation is recommended in order to maintain the level of attention, increase interest and prevent boredom in students, so students always show perseverance, enthusiasm and active participation in learning. Learning strategies as have the meaning as concrete actions or steps that must be taken by teachers and students in setting potential and resources in order to efficiently obtain results in accordance with a design that is composed systemic and systematically so as to support the achievement of objectives. The learning strategy is divided into three types: 1) a strategy of organizing learning content. 2) learning strategies delivery of content: (Exspository strategy) is a learning process conducted by the teachers present the material or subject matter in the form that has been prepared in a neat, systematic and complete, so that the students stayed to listen and observe in an orderly and organized, Strategy Inquiry (startegy inkuiry), namely the delivery of teaching materials that require processing of materials by the students, 3) A management strategy of learning by teachers to create teaching and learning situation and condition so that students do learning activities optimally.